Empirical Analysis of Public Energy Consumption - The Case of a Hungarian Village - Petrovics, Petra; Szilágyi, Roland (Theory, Methodology, Practice – Review of Business and Management, 2011)
Global changes in recent decades have led to a demand to replace natural gas with renewable energy sources. The aim of this study is to prove that natural gas as an energy resource is not affordable in small towns or villages, which have been facing a difficult time because of socio-cultural factors and the lack of economic resources. A village in North Hungary, Csernely was selected, because its geographical and economic conditions are appropriate for implementation of this change. Csernely is a typical Hungarian small village, which is in need of development. We performed a cluster analysis and found that the proportion of ‘household clusters’ reflects the social stratification of villages in Hungary. A long-term goal is to develop an energy supply model based on an alternative resource (such as biomass) that is available on location, is able to substitute for natural gas, and covers fully or partially the heat energy needs of Csernely (Szemmelveisz et al., 2011). The first step is to show that households in Csernely would benefit from the replacement of natural gas. We investigated whether there is any significant difference between the use of gas and solid fuels in the households in Csernely. We found that households are willing to use other alternative energy sources, and that the majority of them have already started to use solid fuels. However, with organized implementation, this can be more efficient and cheaper as well.